Lactobacillus rhamnosus GG in a mixed pineapple (Ananas comosus L. Merril) and jussara (Euterpe edulis Martius) beverage and its survival in the human gastrointestinal tract. (December 2020) - Pires, Bruno de Andrade; Cristina de Almeida Bianchini Campos, Renata; Canuto, John Warnens; de Melo Carlos Dias, Thainá; Furtado Martins, Eliane Maurício; Licursi, Leandro; Ricardo de Castro Leite Júnior, Bruno; Martins, Maurilio Lopes
Abstract: This research aimed to elaborate a mixed beverage containing pineapple and jussara palm fruit and evaluate the viability of Lactobacillus rhamnosus GG (LGG) in the product and also its survival in the human gastrointestinal tract (GIT). In order to evaluate the efficiency of the beverage as a vehicle for LGG, fecal samples from 14 volunteers male were collected before consuming the product, 28 days after intervention, and 42 days after interrupting consumption and they were submitted to LGG count. The mean LGG viability in the beverage was 7.5 log cell/mL (p > 0.05) by flow cytometry, and 6.9 log CFU/mL in the standard plate count. No LGG count was detected in the volunteers feces before consuming the beverage. However, after 28 days of consumption, the mean count of this bacterium in the feces was 7.1 log CFU/g, and 42 days after interrupting consumption, the count had reduced to 4.1 log CFU/g. Thus, the beverage was shown to be feasible as a vehicle for LGG in the GIT of the volunteers, demonstrating the capacity for intestinal colonization. Highlights: The flow cytometry was effective in counting the L. rhamnosus GG in the beverage. The levels of the L. rhamnosus GG were above 10 6 CFU/mL during the 28 days at 8 °C. The beverage was effective as a vehicle for L. rhamnosus GG in the human GIT. Probiotic level was above 10 4 CFU/g in the feces up to 42 days after stop consuming.